FAKTOR PENENTU ADOPSI MEDIA SOSIAL DAN DAMPAKNYA TERHADAP KINERJA PENJUALAN USAHA SEKTOR INFORMAL DI INDONESIA - Syahril Syahril; Fadil Muhammad; Muh. Qardawi Hamzah; Selly Kudrati Ningsih; Farida Islamiah (Universitas Ichsan Sidenreng Rappang, 2026)
The informal sector plays a crucial role in the Indonesian economy, accounting for a significant share of labor absorption. However, it is also closely linked to poverty, low productivity, wage inequality, and limited tax revenue and financial deepening. Social media adoption is seen as a business development strategy, yet the majority of informal businesses have not yet adopted it. This study analyzed the influence of social media on sales and the determinants of adoption using linear regression and probit logistic regression. The results indicate that education, owner age, smartphone ownership, and electricity access influence social media adoption, whereas experience does not. Social media also had no significant impact on the sales of informal sector businesses. Keywords: Informal Sector, Social Media, Sales, Business Actors